La modulación como sistema constructivo en la vivienda social - Guerrón Eras, Gerardo Rafael (2014)
The need to generate a prototype of decent social housing, which meets the basic requirements that families with limited financial resources need to stop living in inhumane conditions is inminent throught our country; as an action against this reality, there has been developed many large scale housing planes, as well as isolated buildings developed by ministries and community support. With this premise, it was thought to analyse different standard dimensions used in several municipalities, national and foreign, to establish the ideal dimensions to build a house, including a detailed analysis of an existing housing program in our town in order to know the architectural model used and finally, to study the modulation as a construction system. Thus, using this results, propose an affordable modular housing prototype, through the use of prefabricated materials which allow to regulate the dimensions of social housing, achieving best quality standards of living, reducing construction time, environmental pollution and costs in construction